2005
DOI: 10.1634/stemcells.2004-0157
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Murine Embryonic Stem Cell Gene Expression Profiles with Functional Measures of Pluripotency

Abstract: Global gene expression profiling was performed on murine embryonic stem cells (ESCs) induced to differentiate by removal of leukemia inhibitory factor (LIF) to identify genes whose change in expression correlates with loss of pluripotency. To identify appropriate time points for the gene expression analysis, the dynamics of loss of pluripotency were investigated using three functional assays: chimeric mouse formation, embryoid body generation, and colony-forming ability. A rapid loss of pluripotency was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
96
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 56 publications
15
96
0
Order By: Relevance
“…2, 3A). These results are consistent with DNA microarray data of others who reported Brf1 (Zfp36L1) downregulation after LIF removal [41,42]. That the effect in some clones was less intense than that following LIF removal suggests that not all effects on gene expression by LIF removal are mediated by Stat3.…”
Section: Discussionsupporting
confidence: 92%
“…2, 3A). These results are consistent with DNA microarray data of others who reported Brf1 (Zfp36L1) downregulation after LIF removal [41,42]. That the effect in some clones was less intense than that following LIF removal suggests that not all effects on gene expression by LIF removal are mediated by Stat3.…”
Section: Discussionsupporting
confidence: 92%
“…However, our study also revealed a specific SB-dependent downregulation of pluripotent ES cell markers such as Rex1, Fbox15 and Pdgfa. 36 Although SB could accelerate cell differentiation and boost apoptosis, by abruptly repressing pluripotent cell markers. At the opposite side, the antiapoptotic PD compound increases expression of survival genes, such as Spp1 gene, recently characterized as a critical self-renewal gene expressed in undifferentiated ES cells.…”
Section: Discussionmentioning
confidence: 99%
“…23 A recent study on the embryonic stem cells showed that NR0B1 is abundantly expressed in an undifferentiated status, but its expression level is down-regulated on differentiation. 24 Knocked down of NR0B1 expression resulted in differentiation of embryonic stem cells, suggesting a role of NR0B1 for the maintenance of undifferentiated state. 25 NR0B1 is expressed in several kinds of cancers, such as endometrial carcinoma, ovarian carcinoma, prostatic carcinoma, and Ewing's sarcoma.…”
mentioning
confidence: 99%